2022
DOI: 10.7554/elife.74765
|View full text |Cite
|
Sign up to set email alerts
|

A plasma membrane-localized polycystin-1/polycystin-2 complex in endothelial cells elicits vasodilation

Abstract: Polycystin-1 (PC-1, PKD1), a receptor-like protein expressed by the Pkd1 gene, is present in a wide variety of cell types, but its cellular location, signaling mechanisms and physiological functions are poorly understood. Here, by studying tamoxifen-inducible, endothelial cell (EC)-specific Pkd1 knockout (Pkd1 ecKO) mice, we show that flow activates PC-1-mediated, Ca2+-dependent cation currents in ECs. EC-specific PC-1 knockout attenuates flow-mediated arterial hyperpolarization and vasodilation. PC-1-dependen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 69 publications
3
37
0
Order By: Relevance
“…These data indicate that clusters observed in TMEM16A ecKO cells are due to background labeling of TMEM16A antibodies, validating the data obtained in TMEM16A fl/fl endothelial cells (Fig. 3A) ( 32 ). Moreover, these results demonstrate that surface TMEM16A and TRPV4 clusters locate in nanoscale proximity, with a sizable proportion exhibiting overlap in the endothelial cell plasma membrane.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…These data indicate that clusters observed in TMEM16A ecKO cells are due to background labeling of TMEM16A antibodies, validating the data obtained in TMEM16A fl/fl endothelial cells (Fig. 3A) ( 32 ). Moreover, these results demonstrate that surface TMEM16A and TRPV4 clusters locate in nanoscale proximity, with a sizable proportion exhibiting overlap in the endothelial cell plasma membrane.…”
Section: Resultssupporting
confidence: 89%
“…Mechanical stimulation with a fluid stream activates a Cl − current in cultured human aortic endothelial cells, although the molecular identity of the channels involved was not determined ( 37 ). Flow stimulates a protein complex composed of polycystin 1 (PKD1) and PKD2 in endothelial cells, leading to eNOS, SK, and IK channel activation and vasodilation ( 4 , 32 ). Flow also stimulates Piezo1, a Ca 2+ -permeant nonselective cation channel, in both arterial and capillary endothelial cells ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in transfected CHO cells revealed unique, PC1 and PC2 co-dependent, calcium-permeable cation currents (Hanaoka et al, 2000). However, the idea of a joint ion channel function for these two proteins did not become widely recognized until the ability of PC1/PC2 to sense fluid shear stress and modulate intracellular calcium levels was demonstrated in cells (Nauli et al, 2003;Alenghat et al, 2004;Nauli et al, 2008;MacKay et al, 2022). Most recently, endothelial cell-specific Pkd1 and Pkd2 knockout mice were used to demonstrate regulation of vasodilation by the PC1/ PC2 complex (MacKay et al, 2022).…”
Section: Polycystin-1 As An Ion Channel Subunitmentioning
confidence: 99%
“…However, the idea of a joint ion channel function for these two proteins did not become widely recognized until the ability of PC1/PC2 to sense fluid shear stress and modulate intracellular calcium levels was demonstrated in cells (Nauli et al, 2003;Alenghat et al, 2004;Nauli et al, 2008;MacKay et al, 2022). Most recently, endothelial cell-specific Pkd1 and Pkd2 knockout mice were used to demonstrate regulation of vasodilation by the PC1/ PC2 complex (MacKay et al, 2022). Formation of an ion channel-like structure consisting of PC1 and PC2 was finally validated by solving the molecular structure of the membraneassociated portions of the two proteins together (Su et al, 2018).…”
Section: Polycystin-1 As An Ion Channel Subunitmentioning
confidence: 99%
“…PKD1 and PKD2 encode Polycystin-1 (PC-1) and Polycystin-2 (PC-2/TRPP2), respectively. PC-1, which functions as a mechanosensor of intraluminal fluid flow, interacts with PC-2/TRPP2, which has calcium (Ca 2+ ) channel activity in its C-terminus [ 12 ]. The PKHD1 gene product fibrocystin/polyductin (FPC) has a long extracellular domain and interacts with the N-terminus of PC-2 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%